Association Between Changes in Depressive Symptoms and Hazardous Drinking: Findings From the Korea Welfare Panel Study (2013–2018) - Jeong, Sung Hoon; Lee, Doo Woong; Kang, Soo Hyun; Kim, Seung Hoon; Park, Eun-Cheol; Shin, Jaeyong (Frontiers in Public Health, 2022)
Objective: This study aimed to evaluate the longitudinal association between changes in depressive symptoms and hazardous drinking among South Korean adults. Participants/Methods: This study was conducted using a sample drawn from participants enrolled in the Korea Welfare Panel Study (KoWePS) from 2013 to 2018. Hazardous drinking was defined as a score of 11 points for men and seven points for women on the Korean version of the Alcohol Use Disorders Identification Test. Depressive symptoms were evaluated using an 11-item version of the Center for Epidemiologic Studies Depression Scale. A generalized estimating equation model was used to analyze the association between changes in depressive symptoms and hazardous drinking. Results: Of the 12,878 people registered with KoWePS and without follow-up losses from 2013 to 2018, a total of 2,341 were included in this study, excluding those under the age of 19 and those with missing data. Persistent depressive symptoms (men, odds ratio [OR]: 2.20, 95% confidence interval [CI]: 1.48–3.21; women, OR: 2.64, 95% CI: 1.66–4.22) and the changes from non-depressive symptoms to depressive symptoms (men, adjusted OR: 2.18, 95% CI: 1.80–2.64; women, OR: 1.71, 95% CI: 1.27–2.29) increased the likelihood of hazardous drinking. Conclusions: Persistent depressive symptoms and changes from non-depressive to depressive symptoms are associated with increased prevalence of hazardous drinking. This suggests that an evaluation of the underlying mental illness or emotion should be made when counseling for abstaining from alcohol for chronic drinkers or the general public.